Effects of blood flow restriction training on blood perfusion and work ability of muscles in elite para-alpine skiers - Geng, Y.; Zhang, L.; Wu, Y. (Medicine & Science in Sports & Exercise, 2022)
Purpose The effects of short-term blood flow restriction (BFR) exercise on muscle blood flow perfusion and performance during high-intensity exercise were determined in elite para-alpine standing skiers to assess whether this would be an effective training regimen for elite athletes with disabilities.